The Role of Active Diplomacy in Achieving the Supreme National Interest of the State - Younis Talat Al-Dabbagh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Most countries have their own strategy in making their foreign policy goals, and in part the tools to achieve those goals, and here comes effective diplomacy as the most important foreign policy tool in today’s era to achieve those goals, especially the higher goals that touch the essence of the state’s supreme national interest, such as those goals that It is linked to the existence of the state, and its national security. Consequently, the more the state relies on a successful strategy in employing effective diplomacy, the more it will succeed in achieving its supreme goals, including the supreme national interest of the state. The supreme national interest of states has also undergone a radical change, so it is not in the interest of states to occupy or annex other lands in today’s world governed by the rules of general international law. Rather, political crises and problems are solved by legal, political and diplomatic methods between countries in today’s world, and diplomats play leading roles in them. In solving it by dismantling and containing it, all of this is due to the existence of an effective diplomatic apparatus, and to the diplomatic qualifications that these diplomats enjoy, both technically and cognitively. Accordingly, diplomatic qualifications are among the necessities of diplomatic work in our world today. It is not sufficient for the state to possess capabilities and capabilities without the presence of distinguished diplomatic figures capable of employing these capabilities and capabilities to achieve the interests of nation states and their higher goals.